2014
DOI: 10.1038/ncb2906
|View full text |Cite
|
Sign up to set email alerts
|

A polarized Ca2+, diacylglycerol and STIM1 signalling system regulates directed cell migration

Abstract: Ca2+ signals control cell migration by regulating forward movement and cell adhesion. However, it is not well understood how Ca2+-regulatory proteins and second messengers are spatially organized in migrating cells. Here we show that receptor tyrosine kinase and phospholipase C signaling are restricted to the front of migrating endothelial leader cells, triggering local Ca2+ pulses, local depletion of Ca2+ in the endoplasmic reticulum, and local activation of STIM1, supporting pulsatile front retraction and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
259
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(271 citation statements)
references
References 69 publications
12
259
0
Order By: Relevance
“…We used tumor mast cells (rat basophilic leukemia cells, RBL‐2H3; Kalesnikoff & Galli, 2008; Wollman & Meyer, 2012) which secrete only part (~30%) of their stored inflammatory agents in response to maximal antigen stimulation (Fig 1A), consistent with the existence of inhibitory pathways that prevent the release of the remaining vesicles. Since previous studies proposed that PKCB is the main PKC isoform regulating mast cell secretion (Nechushtan et al , 2000), we confirmed that inhibition of PKCB with ruboxistaurin (Ishii et al , 1996; Tsai et al , 2014) further reduces the amount of released vesicles in a dose‐dependent manner following stimulation with antigen (Fig 1A) or simultaneous addition of the PKC activators phorbol ester and Ca 2+ ionophore (Fig EV1A).…”
Section: Resultssupporting
confidence: 83%
“…We used tumor mast cells (rat basophilic leukemia cells, RBL‐2H3; Kalesnikoff & Galli, 2008; Wollman & Meyer, 2012) which secrete only part (~30%) of their stored inflammatory agents in response to maximal antigen stimulation (Fig 1A), consistent with the existence of inhibitory pathways that prevent the release of the remaining vesicles. Since previous studies proposed that PKCB is the main PKC isoform regulating mast cell secretion (Nechushtan et al , 2000), we confirmed that inhibition of PKCB with ruboxistaurin (Ishii et al , 1996; Tsai et al , 2014) further reduces the amount of released vesicles in a dose‐dependent manner following stimulation with antigen (Fig 1A) or simultaneous addition of the PKC activators phorbol ester and Ca 2+ ionophore (Fig EV1A).…”
Section: Resultssupporting
confidence: 83%
“…12,13 Sheet migration involves a complex interplay among mechanical forces, molecular interactions and biochemical cascades that are triggered by the exposure of the cellular monolayer to free space, as when cells are exposed to the gap in the wound healing assay. [14][15][16][17][18][19][20][21] Although a strict definition of sheet migration requires cells to maintain intercellular junctions, there is some evidence that cells lacking intercellular junctions such as fibroblasts exhibit some characteristics of sheet migration. 22 The most common information derived from the wound healing assay is the rate of gap closure, which is a measure of the speed of the collective motion of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…These signals are generated by the interplay between Ca 2+ channels, which mediate elevations in cytosolic Ca 2+ and pumps/exchangers, which both temper these elevations and fill Ca 2+ stores. During migration, Ca 2+ gradients form in the cytosol, whereby Ca 2+ levels are lower at the leading edge, likely due to enhanced plasma membrane Ca 2+ ATPase activity (Brundage et al, 1991;Tsai et al, 2014). Much attention has focused on the role of Ca 2+ influx in regulating cell migration.…”
Section: Introductionmentioning
confidence: 99%